Ragusan Antunini Galeazzo Brugnoli from Mantua - Pekić, Radmilo B (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The economic development of Dubrovnik from the end of fourteenth century and the start of textile manufacturing in the second half of fifteenth century encouraged the massive arrival of foreigners. Many Italian experts were motivated by the measures of Ragusan government which offered them privileges, loans and commercial spaces. One of them was Giorgio Brugnoli, a nobleman from Mantua, who had came with his family in Dubrovnik. His son Galeazzo Brugnoli, the subject of this work, once was the most significant textile manufacturer and merchant . Thanks to his business and family reputation he became the member of well-known antunini. In three mandates he led this prominent corporation. Almost the entire life Galeazzo Brugnoli tied to Dubrovnik ,where he formed his family and ended his life. His descendants continued successfully his business until their family died out,227 years after their arrival.